Cliffs as Crosses: The Problematic Symbology of Colin McCahon - Alderton, Zoe (Relegere, 2012)
This paper examines the schism between intended message and reception in the case of New Zealand artist Colin McCahon (1919-1987). McCahon was heavily influenced by Christianity, for him linked inextricably to a message of ecological conservation, and he considered painting to be a prophetic task. As such, McCahon hoped to bring about the religious and behavioural transformation of his audience. McCahon’s Necessary Protection artworks use Christian symbols as a means of communicating the importance of faith as well as his fear of environmental degradation and the necessity of loving one’s homeland. However, McCahon’s complex symbolic lexicon has often proven to be too esoteric to have the intended affect on its intended audience.